Reconstructing Family Takaful in Islamic Law: Toward a Tanāhud-Based Insurance Model - M. Styo Hertinto; Maman Rahman Hakim; Nur Melinda Lestari; ⁠Adam Jehan; ⁠Sofyan Rizal (Universitas Muhammadiyah Bandung, 2026)
Contemporary family takaful has grown significantly, yet its product design remains weakly connected to Islamic family law. Existing models mainly protect against financial risks such as death, disability, health expenses, and education costs, while socio-religious obligations in Muslim family life such as ‘aqīqah, walīmah, uḍḥiyyah, and ta‘zīyah are rarely recognized as relevant dimensions of protection. This study examines the extent to which contemporary family takaful aligns with Islamic family law and maqāṣid al-sharī‘ah, and proposes the tanāhud model as an alternative framework for family-based Islamic insurance. This research employs normative juridical research with conceptual, philosophical, statutory, and maqāṣid-based approaches. Data were obtained from Islamic legal sources, academic literature, regulatory documents, and takaful industry reports, and were analyzed through legal interpretation, conceptual analysis, and maqāṣid-based legal reasoning. The findings show that family takaful is generally compliant at the contractual level but remains substantively limited because it defines risk mainly in financial terms. This limitation reduces its relevance to the socio-religious realities of Muslim families. The novelty of this study lies in reconstructing family takaful through the tanāhud model, which combines tabarru‘, ta‘āwun, tadhamun, and hybrid contractual mechanisms to accommodate both financial and socio-religious family needs. Practically, this model offers guidance for takaful operators to develop more responsive products and for regulators to recognize family-based socio-religious protection within Islamic insurance governance.